Schiff base thorium(iv) and uranium(iv) chloro complexes: synthesis, substitution and oxidation chemistry. Issue 15 (28th March 2017) - Stobbe, Brian C.; Powell, Douglas R.; Thomson, Robert K.
Abstract : Schiff base chloro complexes of U(iv ) and Th(iv ) are prepared and provide access to rare pseudo trans diazide species, and a facile pathway to uranyl complexes through oxidation with NaNO2 . Abstract : New tetradentate Schiff base chloro complexes of U(iv ) and Th(iv ) are prepared by salt metathesis approaches. These compounds undergo clean salt metathesis with NaN3 to generate stable pseudo- trans azide compounds. The uranium dichloro complex also undergoes 2 e − oxidation with excess NaNO2 to generate the uranyl derivative. All classes of complexes are characterized by single crystal X-ray diffraction and NMR spectroscopy.